Agricultural cooperatives in Vietnam and their contributions to benefit the rural poor : a case study in An Giang Province, Vietnam - Pham Trung Tuan; Ahmad, Mokbul Morshed; Routray, Jayant Kumar; Soparth Pongquan; IFP; Ford Foundation; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2007)
The research studied the performance of the agricultural cooperative activities to benefit the poor in An Giang province of Vietnam. The main objectives of the research were to describe the administrative system of agricultural cooperatives in An Giang province; to evaluate the direct benefits and perceptions of the services of the poor farmers on their agricultural cooperatives; to analyze the constraints and opportunities of the agricultural cooperative in terms of providing services and operation for poor farmers in An Giang province; and to give suggestions for the improvement of sharing benefits to poor farmers members of the agricultural cooperatives. The research was conducted with the use of a survey questionnaire at the household level with a total of 70 respondents who were the members of the agricultural cooperative in the study area. The research was focused on a quantitative analysis with the support of qualitative statement. Main findings of the research showed that the performance of the cooperative was quite good in providing services to its members due to enthusiasm of the management committee and staffs, interests from local government, and government support policies. The members perceived quite high degree of benefits and satisfactions from the various activities and services offered by the cooperative. These degrees of benefits and satisfactions of the members were examined in different aspects such as social, economic and institutional aspects in order to explore contributions of the agricultural cooperative to the rural poor. Several problems and constraints were identified in relation to the cooperative's performance. They were limited management capacities of the management committee, lack of operational funds and difficulties in accessibility to credit sources. Certain potentials were identified as the future prospects for further development of the Tan Tien cooperative. Certain recommendations were suggested to improve the performance of the cooperative. These consisted of enhancing efficient management of local committee and the cooperative staffs, encouragement of the exchange with other cooperatives and local institutions for developing leadership skills and increasing members' participation in various cooperative activities.
A research study submitted in partial fulfillment of the requirements for the degree of Master of Science in Regional and Rural Development Planning
Research Studies Project Report (M.Sc.) - Asian Institute of Technology, 2007
Keywords: Agriculture, Cooperative -- Vietnam -- An Giang